1, 2, 4-Triazoline-3, 5-dione substituted perylene diimides as near infrared acceptors for bulk heterojunction organic solar cells. (March 2021) - Liu, Xia; Hu, Ming; Li, Yongle; Zhao, Xiaohong; Zhang, Youdi; Hu, Yu; Yuan, Zhongyi; Chen, Yiwang
Abstract: A series of perylene diimide derivatives (PDIs) with near infrared (NIR) absorption and different geometries were synthesized by introducing 4-phenyl-1, 2, 4-triazoline-3, 5-dione (PTAD) and 4-butyl-1, 2, 4-triazoline-3, 5-dione (BuTAD) to the bay position of PDIs through the Diels–Alder reaction. The compounds with various twisted three-dimensional (3D) structures were obtained through combining different connection units, and their aggregation and domain size of the donor-acceptor blends were adjusted. All of these compounds exhibit broad absorption in the range of 300–860 nm, high thermal stability (with a decomposition temperature over 350 °C), applicable lowest unoccupied molecular orbital energy levels (−3.70 −3.74 eV), and appropriate solubility. Blending with a PM6 polymer donor, bulk heterojunction organic solar cells (BHJ OSCs) based on BDT-SBuTADPDI2 exhibited the highest power conversion efficiency of 2.74%. Their carrier mobility and morphology were investigated by Space-charge-limited current (SCLC) measurements and Atomic Force Microscopy (AFM) measurements respectively. This study provides a promising strategy to construct potential PDI-based acceptors with NIR absorption. Graphical abstract: A series of PDI derivatives with strong near infrared (NIR) absorption (400–870 nm) were constructed and used as acceptors in bulk hetero-junction organic solar cells. Image 1 Highlights: Nine TADPDIs with near infrared absorption were synthesized. Three-dimensional molecular configurations were adjusted through attaching different cores. All target compounds exhibited appropriate solubility, high thermal stability, and applicable energy levels. TADPDIs were used as acceptors in hetero-junction organic solar cells.